Perceived Health Risks among Teachers Working Remotely in the Era of Covid-19 Pandemic - Sheryl Haduca Ramirez (Research Synergy Foundation, 2022)
The COVID-19 pandemic gained prominence and posed a threat to the traditional education system when quarantine was implemented. The teachers' workload increased as work from home was mandated. As a result of working remotely, the teachers experience challenges in their physical, mental, and socio-emotional health. This study evaluated the health risks as perceived by teachers in a tertiary educational institution working remotely during the era of the COVID-19 pandemic in terms of physical, mental, and socio-emotional health. It also aimed to describe the socio-demographic profile of the respondents and determined their current health problems. A cross-sectional descriptive study design was utilized. The respondents were selected using a non-probability convenience sampling technique and data were collected using a researcher-made Likert-type questionnaire adapted from the Occupational Safety and Health Standards by DOLE (2022). Content and construct validity were accomplished through expert reviews and reliability testing was established through a Cronbach alpha coefficient value of 0.950. Data were analyzed using descriptive statistics as well as Z-test and ANOVA for the test of difference. The demographic profile of the respondents indicated a majority belonging to the College of Arts and Sciences, mostly of married civil status, and predominantly female with ages ranging from 41 to 50. The dominant ranks showed Instructors I, II, and III while time engagement in educational technology ranged from 3 hours and above but not greater than 6 hours. The respondents' perceived physical, mental, and socio-emotional health risks revealed a moderate risk as supported by an overall grand mean of 2.629. The physical risk was primarily associated with musculoskeletal problems and had the highest grand mean of 3.038, signifying a moderate level of risk. On the other hand, mental and socio-emotional dimensions were both perceived as low risks, with corresponding grand means of 2.525 and 2.323 respectively. Further results highlighted that level of health risks has a significant difference when grouped according to age (p-value of 0.0012) and academic rank (p-value of 0.0019), thus rejecting the null hypothesis. Sex, marital status, college affiliation, and time engagement in education technology demonstrated no significant difference at all. Health Optimization Practices for Educators (HOPE) was crafted to address health risks by promoting health and wellness through knowledge enhancement. Future studies akin to teachers’ health risks while working remotely need to be explored in the areas of ergonomics and occupational hazards.